Research and innovation impact of entrepreneurship management in Electrical Engineering Faculty / Suzi Seroja Sarnin ... [et al.] - Sarnin, Suzi Seroja; Abdullah, Wan Fazlida Hanim; Naim, Nani Fadzlina; Ya'acob, Norsuzila (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
The huge recent changes in the engineering world have created both challenges and opportunities to the engineering literacy. The engineering faculty is changing to meet these challenges. More and more engineering programs endeavour to include entrepreneurship, innovation and moral values in the engineering curriculum. In this paper, we present our view on entrepreneurship management to future engineers and staff and describe our experience in introducing entrepreneurship in Electrical Engineering Faculty (FKE), Universiti Teknologi MARA, Shah Alam, Malaysia. Entrepreneurship management at FKE has the mandate to equip the students and staff with functional knowledge and skills to build their character, attitude and vision. It has a vital role in developing eco-system that promotes innovation and develops entrepreneurial culture, which drives wealth creation and gives further push to innovations. This necessitates pro-active policy interventions in favour of entrepreneurship. Initiating a fruitful discussion on entrepreneurship management, this paper tries to conceptualise the entrepreneurship education, starting form genesis of term 'entrepreneur', its definition, nature and new role of academic staff and non-academic staff in fostering young entrepreneurs.